Akar-akar Transnasionalisme Islam Hizbut Tahrir Indonesia (HTI) - Masdar Hilmy (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2011)
This paper tries to trace and analyze the roots of?Islamic transnationalism? or ?transnational Islam? in Indonesia through the lens of the three theoretical frameworks that I borrowed from Mandaville as follows: (1) travelling theory; (2) hibridity theory, and; (3) diasphora theory. The paper focuses its analysis on an Islamic movement who carries the ideology of ?Islamic transnationalism? (khil? fah Isl?miyah), namely Hizbut Tahrir Indonesia (HTI). Before delving into the details of HTI?s ideological roots of transnational Islam, however, a conceptual definition of ?transnational Islam? will be elucidated in advance.